The carbon footprint of waste streams in a UK hospital. (1st March 2021) - Rizan, Chantelle; Bhutta, Mahmood F.; Reed, Malcom; Lillywhite, Rob
Abstract: A number of studies have estimated the carbon footprint of healthcare provision in a variety of contexts, but the emission factors used to account for associated waste vary widely and are not healthcare specific. The aim of this study was to estimate and compare the carbon footprint of hospital waste streams. A process-based carbon footprint of hospital waste was estimated in accordance with the Greenhouse Gas Accounting Sector Guidance for Pharmaceutical Products and Medical Devices, using activity data based on waste streams found at three hospitals in one UK National Health Service organisation. This study estimates that the carbon footprint per t of hospital waste was lowest when it is recycled (21–65 kg CO2 e), followed by low temperature incineration with energy from waste (172–249 kg CO2 e). When the waste was additionally decontaminated using an autoclave prior to low temperature incineration with energy from waste, the carbon footprint was increased to 569 kg CO2 e. The highest carbon footprint was associated with the disposal of waste via high temperature incineration (1074 kg CO2 e/ t). NHS data show that the financial cost of waste streams mirror that of the carbon footprint. In conclusion, it is possible to use the carbon footprint of hospital waste streams to derive emission factors for specific waste disposal options. This may inform the optimal processing of healthcare waste in the future. Graphical abstract: Image 1 Highlights: Clinical, anatomical and medicinal waste streams have highest carbon footprint. The choice of waste stream has an up to 50-fold impact on the carbon footprint. Waste streams with lowest estimated carbon footprint have lowest financial costs.